Medio Ambiente y Desarrollo Local, algo más que dos estereotipos - Sotelo Navalpotro, José Antonio (Observatorio Medioambiental, 2008)
This article offers a review of some decentralization related topics, using a more conceptual than empirical approach. In the first section, the ambiguity of the concept of decentralization, often confused with desconcentration and/or delocalization, is described. The second section argues that centralism is a path dependent phenomenon, very related to our countries’ culture. The third section comments current decentralization dynamics, linking them to four forces: Scientific and Technological Revolution, State reform, civil society demands and neoliberalism privatization trends. The fourth section discuss the need of structurating a new cognitive corp, in order to use efficiently the spaces opened by decentralization process, improving territorial growth and development. The last section claims that the modernization of social management of the territory.